Lean Government Applied Concept in Mutation Service over Land and Building Tax at Badan Pendapatan Daerah (Bapenda) South Tangerang, West Java, Indonesia - Agung Hartanto; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2019)
Public service over Regional Government in Indonesia is considered doesn’t good enough. The lean government programs is used to improve public services in Tangerang, West Java, Indonesia. In this study, we analyse the mutation services for object/subject on Land and Building Taxes over Badan Pendapatan Daerah (Bapenda) using lean government concept. The lean government concept is uses the DMAIC mechanism (Define, Measure, Analyze, Improve, and Control). In order to obtain failure mode, we use Failure Mode and Effect Analysis (FMEA) method to improve mutation process service for object/subject on land and building tax. In this study we uses qualitative research method to take the data observation based on interview also documents and records from 30 correspondence. The results showed the applied concept of lean government programs could be increase the submission process of mutation services for object/subjects of Land and Building Taxes to 28.6% with average time reduced 8 days (from 28 days to 20 days).